Especificação e implementação de um protocolo tolerante a falhas e de baixa latência para redes de sensores sem fio - Pazzi, Richard Werner Nelem (2004)
Wireless sensor networks are increasingly being deployed for fine-grain monitoring of physical environments subjected to critical conditions such as fire, leaking of toxic gases and explosions. A great challenge to these networks is to provide a fast, reliable and fault tolerant channel for event propagation. The protocol has to meet the requirements of querybased, event-driven and periodic sensor network application scenarios, even in the presence of emergency conditions that can lead to node failures and path disruption to the sink that receives those events. This paper presents a fault tolerant and low latency routing protocol that meets the sensor networks requirements for critical condition monitoring applications. The algorithm uses the publish/subscribe mechanism and the concept of event driven delivery, a technique that selects the shortest path for the notification of events, reducing latency. Fault tolerance is achieved through the triggering of a local path repair mechanism to find new paths with minimal number of transmissions. The protocol was implemented and simulated in the ns-2 network simulator and compared to the Directed Diffusion paradigm. Relevant metrics, such as end-to-end delay, energy dissipation, and delivery ratio, were evaluated showing that the proposed algorithm can be an adequate solution to meet the strict requirements of information propagation in real-time monitoring applications. An extension of the proposed protocol is also presented. This extension is in phase of implementation and simulation and it is expected to reduce data traffic and, consequently, reduce the energy dissipation. This new solution follows a hierarchical approach to propagate data through the network.